The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11746-013-2364-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of metal triflate catalysts for the trans‐esterification of Jatropha curcas L. oil with methanol and higher alcohols

Abstract: This paper describes an experimental study on the application of metal triflate salts for the (trans‐) esterification of fatty esters (triolein, methyl oleate, methyl linoleate), fatty acid (oleic acid), as well as Jatropha curcas L. oil with methanol and higher alcohols (ethanol, n‐propanol, iso‐propanol, iso‐butanol, tert‐butanol). The effect of the metal type (scandium, bismuth, aluminium, lanthanum, copper, zinc) and process conditions on reaction performance were evaluated. Highest conversions were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…16 For instance, the viscosity of EJO (0.23 Pa s) is about one order of magnitude higher than the viscosity of JO as previously reported in our group (0.034 Pa s). 37 As such, a low viscosity should correspond with a low amount of epoxide groups and this is indeed the case.…”
Section: Synthesis and Properties Of Epoxidized Oils (Eo)mentioning
confidence: 95%
“…16 For instance, the viscosity of EJO (0.23 Pa s) is about one order of magnitude higher than the viscosity of JO as previously reported in our group (0.034 Pa s). 37 As such, a low viscosity should correspond with a low amount of epoxide groups and this is indeed the case.…”
Section: Synthesis and Properties Of Epoxidized Oils (Eo)mentioning
confidence: 95%
“…Another advantage of our catalytic procedure is the mild conditions employed. Under harsher reaction conditions it has been shown that when using an unsaturated FFA, such as OA, isomerisation, and cyclization can occur producing the lactone , and/or butyoxylation of the double bond by the excess butanol . 1 H and 13 C NMR analysis of our esters revealed that no cyclization or butyoxylation of the double bond in OA occurred under the employed reaction conditions (see ESI Figs.…”
Section: Resultsmentioning
confidence: 83%
“…The quality of these oils is shown in Table . Jatropha biodiesel was made from JO4 according to the transesterification method described in L. Daniel et al . The antioxidants with a purity of 95–99.9% were bought from Sigma–Aldrich (Amsterdam, The Netherlands) with exception of Ethanox 4702 (4,4′‐methylenebis‐(2,6‐di‐ tert ‐butylphenol) which was kindly donated by Albemarle (Amsterdam, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%